If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4 = 4x + 23 Reorder the terms: -4 + 7x = 4x + 23 Reorder the terms: -4 + 7x = 23 + 4x Solving -4 + 7x = 23 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 7x + -4x = 23 + 4x + -4x Combine like terms: 7x + -4x = 3x -4 + 3x = 23 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + 3x = 23 + 0 -4 + 3x = 23 Add '4' to each side of the equation. -4 + 4 + 3x = 23 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 23 + 4 3x = 23 + 4 Combine like terms: 23 + 4 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| 11h-7=2h+1 | | Y^3+2y^2=63y | | 28x^2+29x-12=0 | | 4(x+1)=-2(x-3) | | 4(x+1)=-2(x+6) | | 2x+6=8-2x | | 5x+3x=25 | | (48+57)x(61-19)= | | x-5+3x-4=15 | | 28-11x-27x^2+11x^3-1x^4=0 | | (2x-14)*(4-x)*(x^2-1)=0 | | -10p=6p-8 | | -7n-21-8-64n= | | 3.14r^2=314 | | 70-3x=10x | | x^2+3x=x^2+x+2 | | 2x^5+x^4-10x^3-5x^2+8x+4=0 | | (x-a)(x-b)=x^2+x+c | | 12.25-3x^2=6x^2 | | 5x^3-4x^2-11x-2=0 | | 5x+51=x-3 | | 2m+2=10 | | 5x+51=4x+54 | | 2m+1=10 | | 2m+1= | | 3=5m+8 | | m^3+6m^2+9m+4= | | 5x+51=3x-7 | | x+2=2(3x-5) | | 5+3x^2-x^3=0 | | x+0.7+x+0.6=3x-2.3 | | (4x-2)=(3x+18) |